Ascent of the dragon: China's growing role in global affairs. Issue 2 (4th May 2021) - Zaidi, Syed Muhammad Saad; Saud, Adam
ABSTRACT: In contemporary times, the highly debated issue in geopolitics is the rapid rise of China as a potential Superpower. In merely, three decades China's economy has transformed into the second-biggest economy in the world, it has the largest conventional force of the globe, it is now creating international institutes like the Asian Infrastructure Investment Bank to provide a just and balanced alternate economic regime to the US-led liberal order, and it is using its geo-economic might through multi-trillion projects like the Belt and Road Initiative to project its geopolitical influence globally. This paper explains how and when for the first time China came into the limelight as a Major Power. It evaluates China's economic rise; whether it is in a position to become the new economic hub? It assesses the military capabilities of China; does it meet the threshold of a Great Power? It analyses the geostrategic policies adopted by China, especially vis-à-vis the all-important South and East China Seas. Lastly, it determines if China can establish itself as the hegemon in the Eastern hemisphere?